Simulations of foil-based spin-echo (modulated) small-angle neutron scattering with a sample using McStas - Bouwman, Wim G. (International Union of Crystallography, 2021)

(untitled) (J Appl Crystallogr)
For the further development of spin-echo techniques to label elastic scattering it is necessary to perform simulations of the Larmor precession of neutron spins in a magnetic field. The details of some of these techniques as implemented at the reactor in Delft are simulated. First, the workings of the magnetized foil flipper are simulated. A full virtual spin-echo small-angle neutron scattering instrument is built and tested without and with a realistic scattering sample. It is essential for these simulations to have a simulated sample that also describes the transmitted beam of unscattered neutrons, which usually is not implemented for the simulation of conventional small-angle neutron scattering (SANS) instruments. Finally, the workings of a spin-echo modulated small-angle neutron scattering (SEMSANS) instrument are simulated. The simulations are in good agreement with theory and experiments. This setup can be extended to include realistic magnetic field distributions to fully predict the features of future Larmor labelling elastic-scattering instruments. Configurations can now be simulated for more complicated combinations of SANS with SEMSANS.